The Evaluation of the I. G. E. Program in the Windsor Public Schools (Reading) School Year 1973-74. Final Report - Gervase, Charles J.; Lindia, Albert; Windsor Public Schools, CT. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1974)
The Gates-MacGinitie Reading Test and the Culture Fair Intelligence Test were administered to all pupils ages eight to eleven in the Windsor (Connecticut) Public Schools as part of an evaluation of the Individually Guided Education (I. G. E.) program. In this seven-month evaluation, all age groups achieved reading scores significantly higher than those expected of them, as determined by a comparison of their reading scores with the scores predicted by the Bond and Tinker expectancy formula. The data, which are presented in a series of tables, are interpreted as indicating that the reading component of the I. G. E. program was successful and should be continued. (AA)
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Elementary Education; Individualized Instruction; Program Evaluation; Reading Instruction; Reading Programs; Reading Research; Individually Guided Education; Reports, Research